2021
DOI: 10.3390/ijms23010257
|View full text |Cite
|
Sign up to set email alerts
|

Dermal White Adipose Tissue (dWAT) Is Regulated by Foxn1 and Hif-1α during the Early Phase of Skin Wound Healing

Abstract: Dermal white adipose tissue (dWAT) is involved in the maintenance of skin homeostasis. However, the studies concerning its molecular regulation are limited. In the present paper, we ask whether the introduction of two transcription factors, Foxn1 and Hif-1α, into the post-wounded skin of Foxn1-/- mice regulates dWAT during wound healing (days 3 and 6). We have chosen lentivirus vectors (LVs) as a tool to deliver Foxn1 and Hif-1α into the post-wounded skin. We documented that combinations of both transgenes red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
(114 reference statements)
0
10
0
Order By: Relevance
“…Yet, between 3 and 6 dpw there was a near complete loss of lipid and a vast reduction of adipocytes (in the control wounds). The role of lipolysis in wound healing is a recent concept and only a few studies have shown a mechanistic relationship between this phenomena and healing outcomes 38‐41 . Specifically, it has been shown that dermal adipocytes can shed their lipid content and change their fate to a myo‐fibroblast like phenotype 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, between 3 and 6 dpw there was a near complete loss of lipid and a vast reduction of adipocytes (in the control wounds). The role of lipolysis in wound healing is a recent concept and only a few studies have shown a mechanistic relationship between this phenomena and healing outcomes 38‐41 . Specifically, it has been shown that dermal adipocytes can shed their lipid content and change their fate to a myo‐fibroblast like phenotype 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of lipolysis in wound healing is a recent concept and only a few studies have shown a mechanistic relationship between this phenomena and healing outcomes. [38][39][40][41] Specifically, it has been shown that dermal adipocytes can shed their lipid content and change their fate to a myofibroblast like phenotype. 42 This cells then produce ECM and fill in the wound.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Foxn1 activity on the increase in Igf2 expression observed in in vitro experiment was also detected in post‐wounded skin of Foxn1 +/+ mice. Furthermore, our recent in vivo studies showed that lentivirus carrying Foxn1 transgene introduced into post‐wounded skin of Foxn1 −/− mice increases Igf2 expression 78 . A number of studies have found that IGF2 promotes adipogenesis via the IGF‐1R and PI3K pathways, modulates composition of fatty acids in adipose tissue, and participates in CREG1‐mediated glucose uptake 79–81 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our recent in vivo studies showed that lentivirus carrying Foxn1 transgene introduced into post-wounded skin of Foxn1 −/− mice increases Igf2 expression. 78 A number of studies have found that IGF2 promotes adipogenesis via the IGF-1R and PI3K pathways, modulates composition of fatty acids in adipose tissue, and participates in CREG1-mediated glucose uptake. [79][80][81] Interestingly, our recent proteomic analysis revealed that Foxn1 upregulates and stimulates the release of CREG1 protein into conditioned media collected from keratinocytes transduced with Ad-Foxn1.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that Foxn1 regulates reparative (scar-forming) wound healing by engaging in re-epithelialization, epithelial-to-mesenchymal transition (EMT), and dWAT regulation [8]. Our recent data based on a mouse model (Foxn1 +/− and Foxn1 −/− mice) also showed that Foxn1 controls adipogenic signaling that regulates skin homeostasis and wound healing and affects susceptibility to diet-induced obesity [8,24].…”
Section: Introductionmentioning
confidence: 99%

Gender Differences in Post-Operative Human Skin

Gawronska-Kozak,
Kopcewicz,
Machcinska-Zielinska
et al. 2023
Biomedicines
Self Cite